2008
DOI: 10.1353/arc.0.0001
|View full text |Cite
|
Sign up to set email alerts
|

Late Dorset Caribou Hunters: Zooarchaeology of the Bell Site, Victoria Island

Abstract: This paper presents a detailed study of animal bones from a Late Dorset house structure and midden at the Bell site, Victoria Island. Previous research has shown seal to be the staple resource of Late Dorset subsistence in most other regions. Bones of terrestrial mammals such as caribou are rarely found in Late Dorset sites, leading researchers to suggest that Late Dorset people may not have been actively hunting caribou or that caribou population numbers were low during the Late Dorset period across much of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…This finding confirms earlier studies which determined that Dorset economic strategies varied through time and between regions, that differences were likely a response to local conditions and available species, and that no one 'Dorset' subsistence pattern can be defined (Cox, 1978;Cox and Spiess, 1980;Damkjar, 2005;Darwent, 1994Darwent, , 2001Hodgetts et al, 2003;Howse, 2008;Møberg, 1986;Murray, 1999Murray, , 2005Odess, 1998;Spiess, 1978).…”
Section: Isotopic Analysis Of Burial 21supporting
confidence: 88%
“…This finding confirms earlier studies which determined that Dorset economic strategies varied through time and between regions, that differences were likely a response to local conditions and available species, and that no one 'Dorset' subsistence pattern can be defined (Cox, 1978;Cox and Spiess, 1980;Damkjar, 2005;Darwent, 1994Darwent, , 2001Hodgetts et al, 2003;Howse, 2008;Møberg, 1986;Murray, 1999Murray, , 2005Odess, 1998;Spiess, 1978).…”
Section: Isotopic Analysis Of Burial 21supporting
confidence: 88%
“…In some cases, there is an apparent difference in the recovery of fish bones from archaeological sites in comparison with mammals, with the former being under-represented, or presumed to be underrepresented a priori (e.g. Henshaw, 1995;Howse, 2008;Wheeler, 1977;Wheeler and Jones, 1989). In a comparative degradation experiment, Nicholson (1996a) found that fish tended to be more poorly preserved than mammals or birds of comparable size, but was unable to offer an explanation for this pattern.…”
Section: Introductionmentioning
confidence: 99%
“…From 2000 to 2010, the region became the focus of the Iqaluktuuq Project, performed as a collaborative project by the Kitikmeot Heritage Society of Cambridge Bay and the University of Toronto. Over its decade of existence, the Iqaluktuuq project included intensive excavations at more than 10 sites, as well as high-resolution mapping of the region, and contributed material for use by the Kitikmeot Heritage Society in the community of Cambridge Bay (Friesen, 2002(Friesen, , 2004Ryan, 2003Ryan, , 2012Howse, 2005Howse, , 2008Howse, , 2016Griebel, 2010Griebel, , 2013Riddle, 2010).…”
Section: The Bell Site: Late Dorset and Thule Contextsmentioning
confidence: 99%
“…When % MAUs are compared to the caribou food utility index (Metcalfe and Jones, 1988), no significant relationship is found, indicating that elements are not preferentially present, or absent, because of the total amount of meat and marrow attached to them. In addition, all features had element distributions with negative but significant relationships to the meat drying index, possibly indicating that meat was dried at the site and then transported elsewhere for consumption (see Howse, 2008). When caribou element % MAUs were compared with the caribou unsaturated marrow index (Morin, 2007), a positive and significant relationship with this index was identified in each context, though the strength of the relationship varied (TP4; H6M; H6).…”
Section: Element Distributionsmentioning
confidence: 99%